Protective effect of glucagon-like peptide-1 mediated by ultrasound microbubbles on myocardial injury in rats with diabetic cardiomyopathy. Issue 2 (1st February 2022) - Liu, Yanjie; Chen, Li; Wu, Hao; Zhang, Hebin
ABSTRACT: Current study was performed to investigate the therapeutic effects of UTMD combined with Semaglutide, a GLP-1 R agonist, on DCM in GK rats. After 6-week intervention, all rats were examined by conventional echocardiography, and the indicators of papillary muscle horizontal wall were measured. At the end of experiment, the DCM rats were sacrificed, and then blood samples were taken to detect blood lipids and the activities of oxidative stress-related factors in myocardial tissues. Moreover, the myocardial tissues were also taken to observe histomorphological changes and myocardial fibrosis via H&E and Masson staining, respectively. Furthermore, the mRNA and protein levels of PPAR-γ and NF-κB in myocardial tissues were detected. As a result, the glycometabolism and the cardiac functions of DCM rats received combination therapy of GLP-1 R agonist and UTMD were improved. Significantly increased SOD and GSH-Px as well as significantly decreased MDA levels were also observed in rats of combined group compared with others. In addition, both mRNA and protein levels of PPAR-γ and NF-κB were significantly lower than those of the model control ones and Semaglutide microbubbles alone (all P < 0.001). Further pathological histology analysis demonstrated that combination therapy effectively ameliorated fibrosis and myocardial morphological changes of DCM rats. In summary, UTMD combined with Semaglutide can effectively protect cardiac function in rats with DCM by significantly alleviating myocardial fibrosis and oxidative stress. Abbreviations: Ultrasound-targeted microbubble destruction, UTMD; glucagon-like peptide-1 receptor, GLP-1R; diabetic cardiomyopathy, DCM; Goto-Kakizaki, GK; velocity vector imaging, VVI; left ventricular end-diastolic diameter LVIDd; left ventricular end-systolic diameter, LvIDs; left ventricular end-diastolic pressure, LVEDP; fractional shortening, LVFs; left ventricular ejection fraction, LVEF; mean peak radial velocity, Vs; radial strain, Sr; radial strain rate, SRr; superoxide dismutase, SOD; malondialdehyde, MDA; glutathione peroxidase, GSH-Px; peroxisome proliferator-activated receptor-γ, PPAR-γ; nuclear transcription factor κB, NF-κB; insulin resistance, IR; total cholesterol, TC; total triglycerides, TG; creatine kinase, CK; lactate dehydrogenase, LDH; cardiac troponin I, cTnI; collagen volume fraction, CVF; Hematoxylin eosin, H&E.